The Gonadotropin-Inhibitory Hormone: What We Know and What We Still Have to Learn From Fish - Di Yorio, María P.; Muñoz-Cueto, José A.; Paullada-Salmerón, José A.; Somoza, Gustavo M.; Tsutsui, Kazuyoshi; Vissio, Paula G. (Frontiers in Endocrinology, 2019)
Gonadotropin-inhibitory hormone, GnIH, is named because of its function in birds and mammals; however, in other vertebrates this function is not yet clearly established. More than half of the vertebrate species are teleosts. This group is characterized by the 3R whole genome duplication, a fact that could have been responsible for the great phenotypic complexity and great variability in reproductive strategies and sexual behavior. In this context, we revise GnIH cell bodies and fibers distribution in adult brains of teleosts, discuss its relationship with GnRH variants and summarize the few reports available about the ontogeny of the GnIH system. Considering all the information presented in this review, we propose that in teleosts, GnIH could have other functions beyond reproduction or act as an integrative signal in the reproductive process. However, further studies are required in order to clarify the role of GnIH in this group including its involvement in development, a key stage that strongly impacts on adult life.